2002
DOI: 10.1161/hh0202.104109
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral-Directed Expression of the Type 1A Angiotensin Receptor Promotes Cardiomyocyte Hypertrophy via Transactivation of the Epidermal Growth Factor Receptor

Abstract: Abstract-Angiotensin II (Ang II) may cause cardiac hypertrophy via type 1 Ang II receptors (AT 1 ) on cardiomyocytes and through growth factors released from cardiac fibroblasts. Whereas cardiomyocyte-specific AT 1 receptor expression produces cardiac hypertrophy and remodeling in vivo, delineation of the signals that mediate growth to Ang II is challenging because the prevailing in vitro model (cultured neonatal cardiomyocytes) expresses low levels of AT 1 receptor and responds inconsistently to Ang II. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
172
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(182 citation statements)
references
References 51 publications
9
172
0
1
Order By: Relevance
“…Surprisingly, the mechanisms by which AII regulates transcription in the heart remain undefined. Within the heart, AII targets both myocytes and nonmyocytes (64,74). Except for the c-fos gene (61), few direct transcription targets of AII in cardiomyocytes have been identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, the mechanisms by which AII regulates transcription in the heart remain undefined. Within the heart, AII targets both myocytes and nonmyocytes (64,74). Except for the c-fos gene (61), few direct transcription targets of AII in cardiomyocytes have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MAPK signaling did not appear to play a role in relaying AII signaling at the level of the ANF promoter. This may reflect a more specific role for the MAPK pathway in the growth (hypertrophic) effects of AII that are dependent on the EGF receptor (74). In contrast, ANF is a cardioprotective hormone that antagonizes cardiac hypertrophy (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant Dominant Negative FGFR-2 and FGFR-3 Adenoviruses-The pAd-Easy1 virus and shuttle plasmid pAd-TrackCMV were obtained from Dr. R. Hannan, Peter MacCallum Cancer Institute, Melbourne, Australia (24). Adenoviruses expressing dominant negative (DN) FGFR-2␤IIIcAB (devoid of Ig-like domain I and containing the acidic box), FGFR-3␣IIIbAB, and FGFR-3␣IIIcAB (both containing all three Ig-like domains and the acidic box and differing from each other only in the alternate presence of either the IIIb or IIIc exon in the carboxyl terminus of Ig-like domain III) were prepared by amplifying their cDNAs from rat SMC RNA and truncating these cDNAs at the transmembrane domain with the inclusion of a FLAG epitope tag immediately distal to the last amino acid of the transmembrane domain.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that EGFR transactivation plays an important role in cardiovascular remodeling (8,20,(30)(31)(32). It has been reported that activation of ADAM12 (8) or ADAM17 (22) could induce the release of HB-EGF and subsequent EGFR phosphorylation, which may eventually lead to cardiomyocyte hypertrophy, while inhibition of ADAM12 or administration of an HB-EGF neutralizing antibody blocked GPCR agonist-stimulated myocyte hypertrophy (8).…”
Section: Fig 5 Atorvastatin Inhibited the Egfr-erk Signaling Pathwamentioning
confidence: 99%